Elimination of persistent anthropogenic pollutants by micro-mesoporous carbon xerogels. Natural organic matter on surface water and textural properties influences. Issue 1 (February 2021) - Lladó, J.; Lao-Luque, C.; Solé-Sardans, M.; Montemurro, N.; Pérez, S.; Fuente, E.; Ruiz, B.
Abstract: The increase of emerging pollutants (pesticides, pharmaceuticals, iodinated contrast media (ICM), …) in surface and groundwater is a threat to the environment and to human health due to its toxicity and its persistence in water. In this work, the removal of pharmaceuticals and ICM by adsorption onto carbon xerogels and commercial activated carbons with different physicochemical properties is studied. Carbon xerogels have similar micropore volume and BET surface area (0.152 ± 5 cm 3 g −1 and 625 ± 25 m 2 g −1, respectively), with macropore and mesopore volume up to 0.63 cm 3 g −1 and 1.09 cm 3 g −1 and an average pore diameter from 8.8 to 45.6 nm. YAO activated carbon present the highest micropore volume and BET surface area (0.357 cm 3 g −1 and 1092 m 2 g −1, respectively). Small pores favor the pharmaceuticals adsorption and larger pores the uptake of ICM. The presence of polymeric groups in the carbon xerogels and ashes in the HYDC and YAO activated carbons (26.27% and 4.87%, respectively) provides a basic surface for enhancing the adsorption of acidic compounds. All adsorbents have a basic pH (9.3–11.6). The hydrophobicity or hydrophilicity of the adsorbates influences in different ways the adsorption process on porous carbon materials. Natural Organic Matter (NOM) influences in the retention of the pollutants by the carbon materials. There is a competition between the NOM and ICM for the large pores of the carbon xerogels (overall, r > 0.98 amount ICM adsorbed vs. Hg volume intrusion in mesopores). Electrostatic interactions between the natural organic matter and the salicylic and diatrizoic acids have the effect of reducing the quantity adsorbed. Graphical Abstract: ga1 Highlights: Mesopore volume on carbon xerogels up to 1.09 cm 3 g −1 and similar microporosity. ICM adsorption depended by mesoporosity and pharmaceuticals by microporosity. An increase in hydrophobicity decreased the intensity of adsorption. NOM on surface water competed directly with ICM for the mesopores. Electrostatic interactions on the adsorption of acid compounds due to NOM.